PENGARUH GAME ONLINE TERHADAP INTERAKSI SOSIAL SISWA SEKOLAH DASAR - Tatia Nurul Fadilah; Maria Dewi, Sinta; Solahudin Anwar, Aang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of playing online games on the social interaction of elementary school students. The study uses a quantitative approach with a correlational design. The research population consists of 900 students from SDN Sukaharja I, II, and III, while the research sample consists of 90 fourth-grade students determined using Slovin's formula with a 5% margin of error. Data collection techniques include questionnaires on the intensity of playing online games and questionnaires on students' social interaction. Data analysis was conducted using the Pearson Product Moment correlation and simple linear regression. The results of the study indicate that there is a significant relationship between online games and students' social interaction with a correlation coefficient value of r = 0.328 and a significance value of 0.002 (p < 0.05). The coefficient of determination (R²) value of 0.108 indicates that online games contribute 10.8% to students' social interaction, while 89.2% is influenced by other factors beyond research. Thus, online games have a significant influence on the social interaction of elementary school students.